Healing Wounds, Healthy Skin : a Practical Guide for Patients with Chronic Wounds - Reddy, Madhuri (Yale University Press health & wellness., 2011)
Seven million Americans suffer from chronic or slow-healing wounds--this number includes people with diabetes, dementia, paralysis, spinal cord injury, multiple sclerosis, and poor circulation, as well as the elderly and those with reduced mobility. Healing Wounds, Healthy Skin provides patients and caregivers with everything they need to know on the subject, including: Why chronic wounds develop and who is at risk of developing them What "normal healing" is What the different types of wounds are, including those associated with chronic disease How to find appropriate care and get a correct diagnosis What role exercise and nutrition play in treatment and prevention What treatment options are available, from surgery to alternative therapies Also covered are the patients' psychological and emotional experiences, myths about wounds and wound healing, steps to take in an emergency, and a wound patient's bill of rights. With up-to-date information, insightful patient case histories, and a wealth of essential resources, this is the book that chronic wound patients and their caregivers can turn to with confidence